Avaliação subjetiva da função do joelho da sensibilidade proprioceptiva antes e após a reconstrução do ligamento cruzado anterior - Lobato, Daniel Ferreira Moreira (2007)
Several studies have shown the important role of the anterior cruciate ligament (ACL) in the knee proprioception. However, there are still few studies that had evaluate the characteristics of proprioception acuity in the early period of rehabilitation after the ACL-reconstructed surgery, over all when it was associated to functional outcomes. Thus, the objective of this study was to evaluate knee proprioception and subjective knee function in subjects who had an ACL injury, before and after (3 months) the reconstruction surgery with the middle third of patellar tendon autograft; and in control subjects. Ten volunteers who had unilateral ACL injury (26.9±6.8 years) reconstructed group - and fifteen health volunteers (22.1±3.0 years) control group performed a proprioceptive evaluation (joint position sense - JPS during active and passive movements, threshold for detection of passive movement TDPM) on a Biodex Multi-Joint System III Pro isokinetic dynamometer, at 2º/s and at two target-angles (30º and 60º of knee flexion). The variables analyzed were the mean of angular displacement (TDPM) and the mean of absolute error (JPS) in relation to each target-angle. The subjective knee function was evaluated by Lysholm scale. The analyses of variance showed subjective functional deficit in involved limb, compared to the uninvolved limb, as well as in relation to the control group, in both test moments (p<0.01). Although no significant, the results showed a tendency for higher TDPM in the reconstructed group (p=0.06). There was no significant difference in the mean of absolute error between the groups (p>0.05), for any modality of JPS, target-angles or test moments. The TDPM showed strong correlation with the subjective knee functional score (just in the involved limb). Under the experimental conditions utilized, the subjects who had an anterior cruciate ligament injury didn t show proprioceptive deficits in relation to the control group, although of the subjective functional limitations presented.